A phase II feasibility study of carboplatin and nab‐paclitaxel for advanced non‐small cell lung cancer patients with interstitial lung disease (YLOG0114). Issue 9 (23rd March 2022) - Sakashita, Hiroyuki; Uchibori, Ken; Jin, Yasuto; Tsutsui, Toshiharu; Honda, Takayuki; Sakakibara, Rie; Mitsumura, Takahiro; Nukui, Yoshihisa; Shirai, Tsuyoshi; Masuo, Masahiro; Suhara, Kozo; Furusawa, Haruhiko; et al.
Abstract: Background: A standard treatment regimen for advanced non‐small cell lung cancer (NSCLC) patients with interstitial lung disease (ILD) has not been established since most clinical trials exclude such patients because of the high risk of acute exacerbation of ILD. This study aimed to prospectively investigate the efficacy and safety of carboplatin and nab‐paclitaxel as a first‐line regimen for NSCLC patients with ILD. Methods: The enrolled patients had treatment‐naïve advanced NSCLC with ILD. The patients received 4–6 cycles of carboplatin (area under the curve = 5) on day 1 and nab‐paclitaxel 100 mg/m 2 on days 1, 8, and 15 every 4 weeks. The primary endpoint was the completion rate of four or more cycles. Secondary endpoints included toxicity, overall response rate (ORR), disease control rate (DCR), progression‐free survival (PFS), and overall survival (OS). Results: Twenty‐five patients were enrolled in this study. Nine patients had adenocarcinoma, 11 had squamous cell carcinoma, one had large cell carcinoma, and four had NSCLC, not otherwise specified. The completion rate of ≥4 cycles was 76% (95% confidence interval: 56.2%–88.8%), which met the primary endpoint. The ORR and DCR were 44% and 88%, respectively. The median PFS and OS were 5.8 months and 15.8 months, respectively. Three patients experienced grade ≥2 pneumonitis, and one patient met the acute exacerbation criteria. Conclusion: The 4‐week modified regimen of carboplatin and nab‐paclitaxel showed tolerable toxicity with favorable efficacy in NSCLC patients with ILD. This regimen may be an effective treatment option for patients in real clinical settings. Abstract : We performed a phase II feasibility study of carboplatin and nab‐paclitaxel for advanced non‐small cell lung cancer patients with interstitial lung disease. The patients received 4–6 cycles of carboplatin (AUC 5) on day 1 and nab‐paclitaxel 100 mg/m 2 on days 1, 8 and 15 every 4 weeks. The 4‐week modified regimen of carboplatin and nab‐paclitaxel showed tolerable toxicity with favorable efficacy in NSCLC patients with ILD.